Instagram @teensgogreen.id Sebagai Aktivisme Media dalam Isu Lingkungan untuk Generasi Muda - Sekar Kinanthi Prastika; Eni Maryani; Ira Mirawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Digital activism evolves from social movements. The promise of new media in the expansion of digital activism encourages global networks of volunteers to address environmental challenges. The purpose of this article is to investigate how Teens Go Green Indonesia employs new media in digital activism connected to environmental concerns. As a data gathering strategy, a qualitative research methodology including interviews, observation, and documents is employed. The idea of cyberactivism and the theory of new social movements are used to investigate the reality of Teens Go Green Indonesia's various linkages and communication activities. Teens Go Green offers a variety of environmental care initiatives, including fun, camping, and scholarships. Instagram is the most popular platform for spreading information. The type of activism that is carried out is organizationally enabled action by combining connective action and collective action.